ANTAGONISTIC ABILITY OF ENTOMOPATHOGENIC FUNGI METARHIZIUM ANISOPLIAE AND BEAUVERIA BASSIANA AGAINST MORTALITY OF WOOD GRASSHOPPER (VALANGA NIGRICORNIS) - Mohamad, Danial; Lamangantjo, Chairunnisah (Journal of Tropical Mycorrhiza, 2025)
The entomopathogenic fungi Metarhizium anisopliae and Beauveria bassiana are potential biological control agents for suppressing the population of the wood grasshopper (Valanga nigricornis). This study aims to evaluate the antagonistic ability of the fungi M. anisopliae and B. bassiana against the wood grasshopper (Valanga nigricornis). This study is a descriptive study with a quantitative approach, applying inoculum suspension at four concentration levels (P1, P2, P3, and P4) and observing insect mortality and colony growth in culture media. The results showed that the P4 suspension treatment produced the highest mortality of 92% with a probit value of 1.28, while mortality in other treatments ranged from 0 to 75%. The highest infection viability showed that in the P4 treatment, the CFU value was 3.0×106 for M. anisopliae and 1.4×106 for B. bassiana. These findings indicate that high inoculum concentrations increase the antagonistic effectiveness and infection ability of entomopathogenic fungi.